Preparing Anesthesiology Residents for Operating Room Communication Challenges: A New Approach for Conflict Resolution Training. (December 2021) - Birnbach, David J.; Rosen, Lisa F.; Fitzpatrick, Maureen; Shekhter, Ilya; Arheart, Kristopher L.
Abstract : BACKGROUND: The hierarchical culture in high-stake areas such as operating rooms (ORs) may create volatile communication challenges. This unfunded exploratory study sought to establish whether a conflict resolution course was effective in preparing anesthesiology residents to handle and deescalate disagreements that may arise in the clinical environment, especially when challenging a surgeon. METHODS: Thirty-seven anesthesiology residents were assessed for ability to deescalate conflict. Nineteen had completed a conflict resolution course, and 18 had not. The 2-hour course used 10 videotaped vignettes that showed attending anesthesiologists, patients, and surgeons challenging residents in a potentially confrontational situation. Guided review of the videos and discussions was focused on how the resident could optimally engage in conflict resolution. To determine efficacy of the conflict resolution course, we used simulation-based testing. The setting was a simulated OR with loud music playing (75–80 dB) under the control of the surgeon. The music was used as a tool to create a potential, realistic confrontation with the surgeon to test conflict resolution skills. The initial evaluation of the resident was whether they ignored the music, asked for the surgeon to turn it off, or attempted to turn it off themselves. The second evaluation was whether the resident attempted to deescalate (eg, calmly negotiate for the music to be turned off or down) when the surgeon was scripted to adamantly refuse. Two trained observers evaluated residents' responses to the surgeon's refusal. RESULTS: Of the residents who experienced the confrontational situation and had not yet taken the conflict resolution course, 1 of 5 (20.0%; 95% CI, 0.5–71.6) were judged to have deescalated the situation. In comparison, of those who had taken the course, 14 of 15 (93.3%; 95% CI, 68.1–99.8) were judged to have deescalated the situation ( P = .002). Only 2 of 19 (10.5%; 95% CI, 1.3–33.1) of those who completed the course ignored the music on entering the OR versus 10 of 18 (55.6%; 95% CI, 30.8–78.5) who did not complete the course ( P = .004). CONCLUSIONS: This study suggests that a conflict resolution course may improve the ability of anesthesiology residents to defuse clinical conflicts. It also demonstrated the effectiveness of a novel, simulation-based assessment of communication skills used to defuse OR confrontation.